Tinjauan Modal Kerja dalam Pengaruhnya Terhadap Sisa Hasil Usaha (Studi Kasus pada Koperasi Pegawai Pemerintah Provinsi Jawa Barat) - Entang Setiawan; Laely Purnama Sari (IKOPIN, 2020)
This study aims to determine how much influence the Working Capital has on the remaining business results in the Cooperative of West Java Provincial Government Employees for the 2014-2019 Period. The research method used is to use descriptive research methods with quantitative approaches. Data collected is by observation, documentation and literature study techniques. The technique of analyzing data uses normality test, simple linear regression, coefficient of determination, and regression. Based on the results of the study, it is known that there is a significant positive relationship that is very strong between Working Capital and SHU, this is based on the calculation of the correlation coefficient of 0.87 (at an interval of 0.80-100. The magnitude of the influence exerted by the Working Capital variable on Remaining Operating Results is 76%, while the remaining 24% is influenced by other factors not examined.